Light-Emitting Metasurfaces: Simultaneous Control of Spontaneous Emission and Far-Field Radiation - Liu, Sheng; Vaskin, Aleksandr; Addamane, Sadhvikas; Leung, Benjamin; Tsai, Miao-Chan; Yang, Yuanmu; Vabishchevich, Polina P.; Keeler, Gordon A.; Wang, George; He, Xiaowei; Kim, Younghee; Hartmann, Nicolai F.; et al. (Nano Letters, 2018)
Light-emitting sources and devices permeate every aspect of our lives and are used in lighting, communications, transportation, computing, and medicine. Advances in multifunctional and "smart lighting" would require revolutionary concepts in the control of emission spectra and directionality. Such control might be possible with new schemes and regimes of light-matter interaction paired with developments in light-emitting materials. Here we show that all-dielectric metasurfaces made from III-V semiconductors with embedded emitters have the potential to provide revolutionary lighting concepts and devices, with new functionality that goes far beyond what is available in existing technologies. Specifically, we use Mie-resonant metasurfaces made from semiconductor heterostructures containing epitaxial quantum dots. By controlling the symmetry of the resonant modes, their overlap with the emission spectra, and other structural parameters, we can enhance the brightness by 2 orders of magnitude, as well as reduce its far-field divergence significantly.
CRIS-Team Scopus Importer:2023-04-20
Keywords: all-dielectric nanophotonics; dielectric nanoantennas; Fourier imaging; Mie-resonances; spontaneous emission